Periodical concentration of surface plasmon polaritons by wave interference in metallic film with nanocavity array. (June 2021) - Xue, Xiaotian; Fan, Yihang; Segal, Elad; Wang, Weipeng; Yang, Fei; Wang, Yanfeng; Zhao, Fengtong; Fu, Wangyang; Ling, Yunhan; Salomon, Adi; Zhang, Zhengjun
Graphical abstract: Abstract: Metallic thin films with nanocavity arrays provide ideal platforms for plasmonics, non-linear optics, surface chemistry and corresponding applications. A general understanding of electromagnetic (EM) field distributions is needed for further creation, manipulation and designation of near-field enhancements. Herein, we study the distribution of plasmonic hot spots over Ag thin films with triangular nanocavities in hexagonal arrays with a variable of lattice parameters. We propose that the concentration and interference of surface plasmon polaritons (SPP) dominates the distribution of plasmonic hot spots. The localized surface plasmonic resonance (LSPR) at nanocavities excites SPPs to propagate on the thin film, whose concentration and interference lead to an extremely strong near-field enhancement at the surface of the thin film, the location of which can also be termed as plasmonic hot spot. For this model, the calculation results of the physical formula are in excellent agreements with both the experimental results and the electrodynamic simulations with 3D finite element method (FEM). Moreover, the plasmonic hot spots distribute periodically within the nanocavity arrays, determined by the geometric symmetry of the array as well as with the polarization state of the incident field. The periodicity of plasmonic hot spots on flat surface illustrates a new way to concentrate SPPs in an extendable area, which has potential applications in localized non-linear optics, sensing, plasmonic logical circuit and optical computing.